Effect of standard penetration test corrections on the estimation of undrained shear strength - Tan, Jia Jun; Ramli, Harris (Journal of Civil Engineering and Management, 2023)
This paper evaluated the influence of Standard Penetration Test (SPT) correction factors, namely the hammer energy efficiency, borehole diameter, drill rod length, and sampling method, on the correlations between SPT resistance (SPT-N) and undrained shear strength (Su). Comparisons were made between new equations (with and without SPT corrections), which were derived from soil data collected from Penang Island, Malaysia. The coefficient of determination, Absolute Average Relative Error, Standard Deviation, and Analysis of Variance (ANOVA) were employed as the basis for the assessments. Finally, a comprehensive analysis was carried out to evaluate the relationship between uncorrected ratio (Su/N) or corrected ratio (Su/N60) and Plasticity Index (PI)/Liquidity Index (LI). Based on the results, all correction factors recorded a significant impact on the estimated Su, as the ANOVA calculation suggested that the borehole diameter correction was the most statistically significant. Furthermore, the Su/N and Su/N60 exhibited increasing trends with increased PI and LI, which may be attributed to the soil’s state and behaviour. Additionally, cubic regression is the best-fit equation to correlate the parameters. In summary, this study provided new insights into the influence of correction factors, which can be used to improve the accuracy of the empirical correlations and engineering designs.